Nanocellulose for peripheral nerve regeneration in rabbits using citric acid as crosslinker with chitosan and freeze/thawed PVA. (13th August 2021) - de Lima, Gabriel G; Júnior, Emílio L de S; Aggio, Bruno B; Shee, Bor Shin; Filho, Emanuel M de M; Segundo, Francisco A de S; Fournet, Margaret B; Devine, Declan M; Magalhães, Washington L E; de Sá, Marcelo J C
Abstract: This work investigates peripheral nerve regeneration using membranes consisting of pure chitosan (CHI), which was further blended with nanofibrillated cellulose, with citric acid as crosslinker, with posterior addition of polyvinyl alcohol, with subsequent freeze thawing. Nanocellulose improves the mechanical and thermal resistance, as well as flexibility of the film, which is ideal for the surgical procedure. The hydrogel presented a slow rate of swelling, which is adequate for cell and drug delivery. A series of in vitro tests revealed to be non-toxic for neuronal Schwann cell from the peripheral nervous system of Rattus norvegicus, while there was a slight increase in toxicity if crosslink is performed—freeze-thaw. The in vivo results, using rabbits with a 5 mm gap nerve defect, revealed that even though pure CHI was able to regenerate the nerve, it did not present functional recovery with only the deep pain attribute being regenerated. When autologous implant was used jointly with the biomaterial membrane, as a covering agent, it revealed a functional recovery within 15 d when cellulose and the hydrogel were introduced, which was attributed to the film charge interaction that may help influence the neuronal axons growth into correct locations. Thus, indicating that this system presents ideal regeneration as nerve conduits.